A case of sirenomelia in one of a pair of identical twins, and in association with exomphalos - Oğuz, Aynur; Gökalp, Ayşe; Gültekin, Asım; Örsal, Metin (The Turkish Journal of Pediatrics, 1986)
A case of sirenomelia with exomphalos in one of a pair of identical twins is described. Radiological examination revealed eight cervical and six lumbar vertebrae, a small pelvis, agenesis of the right ileum, a hypoplastic sacrum and mandibulofacial dysplasia. Autopsy findings included a single umbilical artery, aplasia of the right and hypoplasia of the left kidney, absence of the renal artery, of both ureters, the bladder, the urethra and the rectum.
Keywords: caudal regression syndrome; exomphalos; sirenomelia